Economic viability for different coffee harvest systems - Cunha, Joao Paulo Barreto; da Silva, Fabio Moreira; Dias, Rodrigo Elias Batista Almeida; Lisboa, Cristiane; Machado, Tulio de Almeida (Coffee Science - ISSN 1984-3909, 2016)
This study was conducted to analyze the technical and economic viability for different coffee crops harvest systems, applied in Southern Minas Gerais, Brazil. In the harvest of 2014, the operational performance of three mechanic harvest systems for coffee trees were evaluated, as well as their productivity and operational costs, compared to manual and semi-mechanic systems. Based on data outcome, it is possible to assure that the mechanic harvest for coffee trees yields greater cost reduction and an increase in productivity in relation to other systems, and it is either economically viable. Soil declivity is an influencing factor on productivity for mechanic systems, and harvesters that work under such conditions suffer a decrease in operational efficiency and productivity, due to a higher demand of time during harvest.